Interactions of Sulfate with Other Nutrients As Revealed by H2S Fumigation of Chinese Cabbage - Reich, Martin; Shahbaz, Muhammad; Prajapati, Dharmendra H.; Parmar, Saroj; Hawkesford, Malcolm J.; De Kok, Luit J. (Frontiers in Plant Science, 2016)
Sulfur deficiency in plants has severe impacts on both growth and nutrient composition. Fumigation with sub-lethal concentrations of H2S facilitates the supply of reduced sulfur via the leaves while sulfate is depleted from the roots. This restores growth while sulfate levels in the plant tissue remain low. In the present study this system was used to reveal interactions of sulfur with other nutrients in the plant and to ascertain whether these changes are due to the absence or presence of sulfate or rather to changes in growth and organic sulfur. There was a complex reaction of the mineral composition to sulfur deficiency, however, the changes in content of many nutrients were prevented by H2S fumigation. Under sulfur deficiency these nutrients accumulated on a fresh weight basis but were diluted on a dry weight basis, presumably due to a higher dry matter content. The pattern differed, however, between leaves and roots which led to changes in shoot to root partitioning. Only the potassium, molybdenum and zinc contents were strongly linked to the sulfate supply. Potassium was the only nutrient amongst those measured which showed a positive correlation with sulfur content in shoots, highlighting a role as a counter cation for sulfate during xylem loading and vacuolar storage in leaves. This was supported by an accumulation of potassium in roots of the sulfur-deprived plants. Molybdenum and zinc increased substantially under sulfur deficiency, which was only partly prevented by H2S fumigation. While the causes of increased molybdenum under sulfur deficiency have been previously studied, the relation between sulfate and zinc uptake needs further clarification.